Surgical Outcomes of a Combined Surgical Approach for Apical Prolapse Repair - Brito, Luiz Gustavo Oliveira; Cohen, Sarah Lauren; Tusheva, Olga; Kohli, Neeraj; Morse, Abraham; Goggins, Emily Rose; Einarsson, Jon Ivar (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2016)
Introduction We aimed to evaluate the safety, efficacy and surgical outcomes of combined laparoscopic/vaginal prolapse repair by two surgeons.Material and Methods A retrospective chart review of all patients (n = 135) who underwent apical prolapse repair from February 2009 to December 2012 performed in a collaborative manner by a Minimally Invasive Gynecologic Surgeon and a Urogynecologist. Demographic data (age, body mass index [BMI], race, gravidity, parity) and surgical information (estimated blood loss, operative time, intraoperative complications, readmission and reoperation rates, presence of postoperative infection) were collected.Results The majority of patients were postmenopausal (58.91%), multiparous (mean parity = 2.49) and overweight (mean BMI = 27.71). Nearly 20% had previous prolapse surgery. The most common surgical procedure was laparoscopic supracervical hysterectomy (LSH) with sacrocervicopexy (59.26%), and the most common vaginal repair was of the posterior compartment (78.68%). The median operative time was 149 minutes (82–302), and the estimated blood loss was 100 mL (10–530). Five intra-operative complications, five readmissions and four reoperations were noted. Performance of a concomitant hysterectomy did not affect surgical or anatomical outcomes.Conclusion Combination laparoscopic/vaginal prolapse repair by two separate surgeons seems to be an efficient option for operative management.
Keywords: sacrocolpopexy; operative time; combined surgery; apical prolapse